2022
DOI: 10.3390/molecules27030676
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Potential of Ponciri Fructus: Effects of Extracts, Fractions and Compounds on Adipogenesis in 3T3-L1 Preadipocytes

Abstract: Background: Ponciri Fructus, a crude drug consisting of the dried immature fruits of Poncirus trifoliata (L.) Raf., is a popular folk medicine used for the treatment of allergy and gastrointestinal disorders in Korea and China. In this study, the anti-adipogenic activity of extracts and isolated compounds were evaluated using 3T3-L1 preadipocytes. Methods: Dried immature fruits were extracted and fractionated into n-hexane, ethyl acetate (EtOAc), n-butanol and water-soluble fractions. The ethanol extract and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 75 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…PFI has various pharmacological properties such as antiallergy, antitumor, antiviral, and anti-inflammatory effects ( 16 20 ). PFI contains high amounts of various compounds, including flavonoids (naringin, neoponcirin, and poncirin) and coumarins (umbelliferone, imperatorin, and auraptene), which have various pharmacological activities, including anticancer and anti-inflammatory effects ( 24 , 25 ). Naringin exhibited anti-inflammatory, antioxidant, and antiapoptotic effects in treating LPS-induced cardiac injury ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFI has various pharmacological properties such as antiallergy, antitumor, antiviral, and anti-inflammatory effects ( 16 20 ). PFI contains high amounts of various compounds, including flavonoids (naringin, neoponcirin, and poncirin) and coumarins (umbelliferone, imperatorin, and auraptene), which have various pharmacological activities, including anticancer and anti-inflammatory effects ( 24 , 25 ). Naringin exhibited anti-inflammatory, antioxidant, and antiapoptotic effects in treating LPS-induced cardiac injury ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that PFIE improves insulin resistance by regulating macrophage-mediated inflammation and enhances glucose and lipid metabolism in high-fat diet-induced obese mice ( 24 ). Moreover, PFIE has shown strong anti-adipogenic activity by downregulating the adipogenic markers, such as peroxisome proliferator-activated receptors proteins γ, sterol response element binding proteins-1, and CCAAT/enhancer binding proteins α ( 25 ). However, the effects of PFI on sepsis remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has been related to additional metabolic diseases such as insulin resistance, NAFLD, T2D, dyslipidemia, cardiovascular diseases, hypertension, and cancer [ 90 ]. Adipose tissue growth results in fat storage in pre-existing adipocytes and the transformation of preadipocytes into mature adipocytes, a process called adipogenesis [ 91 ]. Under adipogenic conditions, more amount of free fatty acids will be produced by hypertrophic adipocytes [ 92 ].…”
Section: Mechanism Of Ck Against Metabolic Diseasesmentioning
confidence: 99%
“…Among these, esculin [32,33], scopoline [34,35], caffeic acid [36,37], fraxetin [38,39], scopoletin [40,41], isofraxidin [42,43], scoparone [44,45] and imperatorin [46,47] have been previously reported to exhibit hepatoprotective effects, along with inhibitory effects on osteoclastogenesis or anti-osteoporotic effects. Furthermore, bergapten has been demonstrated to hinder osteoclast differentiation and mitigate bone loss in OVX mice [48], while oxypeucedanin and phellopterin have exhibited anti-obesity properties [49]. Therefore, the principal active compounds accountable for the bone-protective and hepatoprotective effects of WEAD encompass esculin, scopoline, caffeic acid, fraxetin, scopoletin, isofraxidin, scoparone, imperatorin, bergapten, oxypeucedanin and phellopterin.…”
Section: Phytochemical Constituents Of Weadmentioning
confidence: 99%
“…while oxypeucedanin and phellopterin have exhibited anti-obesity properties [49]. Therefore, the principal active compounds accountable for the bone-protective and hepatoprotective effects of WEAD encompass esculin, scopoline, caffeic acid, fraxetin, scopoletin, isofraxidin, scoparone, imperatorin, bergapten, oxypeucedanin and phellopterin.…”
Section: Phytochemical Constituents Of Weadmentioning
confidence: 99%